Benefit-Risk Assessment of Off-Label Drug Use in Children: The Bravo Framework - Van Der Zanden, Tjitske M.; Mooij, Miriam G.; Vet, Nienke J.; Neubert, Antje; Rascher, Wolfgang; Lagler, Florian B.; Male, Christoph; Grytli, Helene; Halvorsen, Thomas; De Hoog, Matthijs; De Wildt, Saskia N. (Clinical Pharmacology & Therapeutics, 2021)
A drug is granted a license for use after a thorough assessment of risks and benefits based on high-quality scientific proof of its efficacy and safety. Many drugs that are relevant to children are not licensed for use in this population implying that a thorough assessment of risks and benefits in the pediatric population has not been made at all, implying a negative risk-benefit balance in children, or implying insufficient information to establish the risk-benefit balance. Use of drugs without positive assessment of risks and benefits exposes children to potential lack of efficacy, unknown toxicity, and harm. To aid guideline committees and individual prescribers, we here present a tutorial of the Benefit and Risk Assessment for Off-label use (BRAvO) decision framework. This pragmatic framework offers a structured assessment of benefits and risks of off-label drug use, including a clinical pharmacological based approach to age-appropriate dose selection. As proof of concept and to illustrate the practical use, we have applied the framework to assess benefits and risks of off-label use of ondansetron for gastroenteritis-induced nausea and vomiting. The framework could also guide decisions on off-label use in other special populations (e.g., pregnant women, elderly, obese, or critically ill patients) where off-label drug use is frequent, thereby contributing to effective and safe pharmacotherapy.
CRIS-Team WoS Importer:2021-08-13